2017
DOI: 10.1111/1346-8138.14145
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term clinical efficacy and safety of secukinumab for Japanese patients with psoriasis: A single‐center experience

Abstract: Secukinumab is a fully human monoclonal antibody that can selectively neutralize interleukin-17A, and its excellent efficacy has been demonstrated in clinical trials for psoriasis. The aim of our study is to assess long-term efficacy and safety of secukinumab for 52 weeks in real-world clinical practise in our facility. A total of 83 patients (71 with psoriasis vulgaris and 12 with psoriatic arthritis) were included, and 49 of them were bio-switched patients. Psoriasis Area and Severity Index (PASI) 75 and PAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 11 publications
4
29
1
Order By: Relevance
“…Our data showed similar results. One study with 83 patients who were studied for 12 months showed higher drug survival in bio‐experienced patients than in bio‐naive patients despite no statistical significance . This may be due to the relatively small cohort and short study period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data showed similar results. One study with 83 patients who were studied for 12 months showed higher drug survival in bio‐experienced patients than in bio‐naive patients despite no statistical significance . This may be due to the relatively small cohort and short study period.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding secukinumab, drug survival was reported in 83-368 enrolled patients in observation periods ranging from 12 months to 3 years and 4 months. [8][9][10][11] The 12-and 18-month overall drug survivals of secukinumab were 76-83% and 67-78.8%, respectively, and higher drug survival was shown in bio-na€ ıve patients than in bio-experienced patients with or without statistical significance. [8][9][10] Our data showed similar results.…”
Section: Discussionmentioning
confidence: 99%
“…Although other real-world Canadian (33), German (34), Italian (35), Japanese (36), and Spanish (37) studies have reported comparable effectiveness of secukinumab in patients with psoriasis between reported clinical trial data and real-world data, there is a lack of real-world studies in the United States assessing the effectiveness of secukinumab. This study provides results of the effectiveness of secukinumab in a real-world setting and may contribute to physician decisions regarding treatment selection in routine clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Although secukinumab has been shown to be well tolerated and effective in treating patients with plaque psoriasis and PsA in multiple clinical trials (7-9,29-34) with up to 5-year follow up (35), randomized controlled trials are likely to enroll patient populations with more stringent inclusion/exclusion criteria and generally the study design allows a short-term observation compared to the real-world setting. A variety of real-world studies have been recently published: some of them analyzed secukinumab drug survival (36)(37)(38)(39), whereas others assessed its efficacy in psoriasis patient populations with peculiar features, or assessing its effectiveness as improvement of DLQI, BSA, PGA, and PASI scores (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Nevertheless, they reported favorable secukinumab safety and effectiveness in terms of mean reduction of PASI value over time, as patient rates achieving PASI 75, PASI 90, and PASI 100 responses at different timepoints, Investigator's Global Assessments or improvements in quality of life measures (11)(12)(13)(14)(15)(16)(17)(18)(19)22).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some real-world studies describing the effectiveness and safety of secukinumab have been published, but only one study included data on the absolute residual PASI score (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Indeed, the effectiveness of antipsoriatic treatments is usually reported as the relative 75%, 90%, or 100% improvement from baseline on the Psoriasis Area Severity Index (PASI 75, PASI 90, PASI 100), though there is emerging interest in the evaluation of absolute PASI score reduction as a better benchmark of therapeutic response and the higher clinical relevance of the remaining absolute PASI score as therapeutic target (i.e.…”
Section: Articlementioning
confidence: 99%